Picturesque ekphrasis in the subjective structure of the lyrical cycle of S. Gandlevsky - Elena V. Abramovskikh (Семиотические исследования)
The purpose of the article is to study the role of pictorial ekphrasis in the subjective structure of the lyrical text. The chosen direction allowed us to consider the relationship between different types of art, to reveal the possibilities of the poetic word in conveying pictorial images, and to problematize the boundaries of the subject/addressee/reader in the text. Based on the material of the non-authorial lyrical cycle by S. Gandlevsky: "Cigarettes are a small hell" (1973), "It was so sad, as if we were step by step..." (1976), "Usually three blows are enough for me" (2012), the perception of Bruegel’s painting "Hunters in the Snow" by the lyrical subject is examined. It is shown that in each of the poems the point of view of the lyrical subject changes, and accordingly the perspective of understanding the picture, immersion in the world created by the artist, and generation of a "one’s own" world. Self-identification of the lyrical subject occurs through involvement, living through Bruegel’s plot to estrangement.